El balance entre eficiencia y equidad en las intersecciones semaforizadas (2020)
There are multiple ways to optimize a signalized intersection, the optimization can be done multi-objective, in saturated or unsaturated conditions, and in a single intersection or in several. What we have in common is that since transport and traffic are non-deterministic systems, it is necessary to perform multiple simulations at the same time to be able to determine that an optimum was reached. The objective of this thesis is to create a program capable of obtaining the indicators necessary to evaluate an intersection given the information of flows, restrictions, and capabilities of any given intersection. These indicators are obtained via multiple PTV Vissim simulations made from matlab.